A synthesis and performance evaluation of a highly efficient ecological dust depressor based on the sodium lignosulfonate–acrylic acid graft copolymer. Issue 21 (22nd March 2018) - Liu, Yanghao; Nie, Wen; Mu, Yubing; Zhang, Haihan; Wang, Hongkun; Jin, Hu; Liu, Zhiqiang
Abstract : In this paper, a highly efficient and environmentally-friendly dust depressor was developed based on the sodium lignosulfonate–acrylic acid graft copolymer. Abstract : In this paper, a highly efficient and environmentally-friendly dust depressor was developed based on the sodium lignosulfonate–acrylic acid graft copolymer. Using the grafting ratio as an index, a three-factor and four-level orthogonal experiment was conducted to optimize the fabrication conditions of the graft copolymer. At a reaction temperature of 60 °C, feed ratio m SLS–AA of 1 : 3, and FeSO4 ·7H2 O content of 2.5%, the prototype produced the highest grafting ratio. The microstructure of the graft copolymer was measured using Fourier transform infrared spectrometry (FTIR) and nuclear magnetic resonance ( 1 H-NMR). Furthermore, the influence of glycerol and the JFC penetrant on the contact angle between the compound solution and coal powder was investigated. Finally, four formulas of dust depressor were selected based on the experimental results. The dust-control performance of the four dust depressors was then tested on a large-scale spray dust suppression simulation platform. The results show that after applying formula 1 at various distances from the spray field, the average dust reduction rates of the total dust (respirable dust) at each point increased. Compared to the water-spraying dust suppression technique, the dust concentration is significantly reduced after the graft copolymer dust depressor is applied.